2022
DOI: 10.3390/ijerph191710984
|View full text |Cite
|
Sign up to set email alerts
|

Coupling and Coordinative Development of Green Finance and Industrial-Structure Optimization in China: Spatial-Temporal Difference and Driving Factors

Abstract: Although the literature has studied the direction and extent of the effect of green finance on industrial-structure optimization, quantitative analysis of the coupling coordination and spatial–temporal differences between green finance and industrial structure is relatively scarce. Therefore, in this paper, we built the theoretical framework of the coupling coordination relationship between green finance and industrial-structure optimization, and then we used the coupling coordination degree and geographic det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The study's findings align with prior research that has underscored the significance of technological innovation in fostering the adoption of renewable energy sources. Multiple studies have demonstrated that advancements in renewable energy technology and innovations play a significant role in fostering the acceptance and expansion of renewable energy sources [103,[138][139][140][141]. Moreover, the correlation between technical innovation and the utilization of renewable energy is in line with global initiatives and legislative measures aimed at promoting the adoption of renewable energy sources.…”
Section: Discussionmentioning
confidence: 98%
“…The study's findings align with prior research that has underscored the significance of technological innovation in fostering the adoption of renewable energy sources. Multiple studies have demonstrated that advancements in renewable energy technology and innovations play a significant role in fostering the acceptance and expansion of renewable energy sources [103,[138][139][140][141]. Moreover, the correlation between technical innovation and the utilization of renewable energy is in line with global initiatives and legislative measures aimed at promoting the adoption of renewable energy sources.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have examined how green finance initiatives including loans and investments optimize and shift industrial sectors toward sustainability. These findings are crucial for governments and business stakeholders seeking financial incentives for eco-friendly operations [12,31,46,57,85,96,124,130,139].…”
Section: Fig 10 Themes Of Green Financementioning
confidence: 96%